Permanent Employee Assessment Decision Support System using the Simple Multi Attribute Rating Technique (SMART) Method - Ryan A Pratama; Romi Hardianto (Universitas Putra Indonesia YPTK Padang, 2024)
Every agency or organization must be able to select and determine competent employees to fill vacant positions so that the main duties of that position can be carried out. To obtain information quickly and accurately about the assessment of permanent employees in accordance with the expected criteria, a decision support system is needed. Objective decisions are usually fair because they are in accordance with the facts and supported by data to produce a decision/recommendation that can make things easier for agency or organization leaders. By using the Simple Multi Attribute Rating Technique (SMART) method, it is hoped that it can help in making decisions about evaluating permanent employees. The SMART method uses a multiattribute decision technique which is used to support decision makers in choosing between several alternatives. This research aims to assist the leadership of the West Sumatra Ministry of Religion in making decisions regarding permanent employee recommendations for employees. The method used in this research is qualitative. Based on the test results, a weighting system is produced that takes into account the assessment factors that exist in employees. The results of the assessments that have been carried out will immediately produce data on employees who have competencies worthy of being promoted to a better career level. In the research, 6 criteria were used, namely cooperation , work ability, work discipline, loyalty, responsibility and communication. With 5 alternative data, calculations were carried out using the SMART method, the result that got the highest score was Endang Mesfitra with a final result of 0.7425. With the research results, the application can help leaders in providing assessments and the results of these assessments produce objective decisions so that leaders can recommend employees according to the criteria